2019
DOI: 10.3390/plants8030070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Root System Characteristics on Black Spruce Seedling Responses to Limiting Conditions

Abstract: Roots directly affect planted seedling adaptation to new growing conditions at reforestation sites. To test the influence of root characteristics on the short-term response of seedlings to limiting resources (water, nutrient, or oxygen), we conducted two experiments. We compared (1) the growth and physiology of three types of four-year-old black spruce (Picea mariana (Mill.) BSP) seedlings (Containerized, highly developed initial roots restricted to a plug; bareroot, less developed but unrestricted initial roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
(99 reference statements)
0
4
0
1
Order By: Relevance
“…Below the planting depth of −3 cm, a common practice in eastern Canada, the growth of the vertical seedlings was greater than the non-vertical seedlings. The advantage of the non-vertical seedlings above this threshold was probably the result of the growth of adventitious roots in contact with the moist soil [69,70].…”
Section: Seedling Growthmentioning
confidence: 99%
“…Below the planting depth of −3 cm, a common practice in eastern Canada, the growth of the vertical seedlings was greater than the non-vertical seedlings. The advantage of the non-vertical seedlings above this threshold was probably the result of the growth of adventitious roots in contact with the moist soil [69,70].…”
Section: Seedling Growthmentioning
confidence: 99%
“…A study on Central Amazonian trees, such as Salix martiana and Tabernaemontana juliana, demonstrated that the main entry point of atmospheric oxygen was gas-permeable pores in the stem, near the origin of adventitious roots (Haase & Rätsch, 2010). Evidence of the role of adventitious roots in the survival of waterlogged trees is also available from temperate regions of the world, with species such as Larix laricina, Platanus occidentalis, and Picea mariana showing strong tolerance to flooding by investing in adventitious roots (Tsukahara & Kozlowski, 1985;Calvo-Polanco et al, 2012;Pernot et al, 2019). For Alnus rubra, Batzli and Dawson (1997) observed a drop in stomatal conductance during the process of investing in adventitious roots when flooded.…”
Section: Discussionmentioning
confidence: 99%
“…Lo cual indica la buena calidad y funcionalidad de las raíces adventicias formadas en las estacas. La morfología de raíces tiene gran relevancia en los procesos de aclimatación que definen el establecimiento y supervivencia de las plantas en condiciones de campo (Pernot et al 2019). Por lo que, es necesario continuar la evaluación del desarrollo y crecimiento de las plantas enraizadas en condiciones de campo, para complementar la información y proponer el uso de esta técnica en la producción de plantas de P. hartwegii.…”
Section: Discussionunclassified